The Impact of Yuan Internationalization on the Euro-Dollar Exchange Rate - Agnes Benassy-Quere; Yeganeh Forouheshfar (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the implication of a multipolarization of the international monetary system on cross-currency volatility. More specifically, we analyze whether the internationalization of the yuan could modify the impact of asset supply and trade shocks on the euro-dollar exchange rate, within a three-country, three-currency portfolio model. Our static model shows that the internationalization of the yuan (defined as a rise in the yuan in international portfolios) would be either neutral or stabilizing for the euro-dollar rate, whatever the exchange-rate regime of China. Moving to a dynamic, stock-flow framework, we show that the internationalization of the yuan would make exchange-rate variations more efficient to stabilize net foreign asset positions after a trade shock.
Keywords: F31; F33; 330; China; yuan; exchange-rate regime; euro; dollar